Tax Minimization sebagai Pemoderasi Determinan Praktik Transfer Pricing - Hartinah, Siti; Fitria, Aldina (Jurnal Akuntansi dan Governance, 2024)
Objectives: Testing tax minimization as a moderator of the impact of tax burden, profitability and tunneling incentives in influencing transfer pricing practices.Design/method/approach: Associative quantitative approach. Population of coal subsector industrial companies registered on the IDX for the 2017-2021 period. From the Purposive Sampling technique of 11 companies over five years, a total of 55 data were observed. Moderated regression analysis with panel data and analysis tools, namely E-views software.Results/findings: Tax minimization as a potential moderating variable is able to moderate the tax burden on transfer pricing practices insignificantly. Profitability and Tunneling Incentives have a significant positive influence on transfer pricing practices. Meanwhile, tax burden and tax minimization have no influence on transfer pricing practices.Theoretical contribution: These findings are able to prove that transfer pricing practices can be influenced by internal and external factors of the Company and support agency theory regarding conflicts of interest between the Company, shareholders and the government regarding aspects of taxation and transfer pricing and become a reference for further research.Practical contribution: Become a reference for the tax authorities or DJP in formulating policies regarding tax regulations related to transfer pricing by providing strict and more detailed supervision for companies that carry out transfer pricing.Limitations: Moderating variables are not used to moderate all independent variables in influencing the dependent variable.